Deleterious mtDNA mutations are common in mature oocytes. Issue 3 (17th October 2019) - Ma, Hong; Hayama, Tomonari; Van Dyken, Crystal; Darby, Hayley; Koski, Amy; Lee, Yeonmi; Gutierrez, Nuria Marti; Yamada, Satsuki; Li, Ying; Andrews, Michael; Ahmed, Riffat; Liang, Dan; et al.
Abstract: Heritable mitochondrial DNA (mtDNA) mutations are common, yet only a few recurring pathogenic mtDNA variants account for the majority of known familial cases in humans. Purifying selection in the female germline is thought to be responsible for the elimination of most harmful mtDNA mutations during oogenesis. Here we show that deleterious mtDNA mutations are abundant in ovulated mature mouse oocytes and preimplantation embryos recovered from PolG mutator females but not in their live offspring. This implies that purifying selection acts not in the maternal germline per se, but during post-implantation development. We further show that oocyte mtDNA mutations can be captured and stably maintained in embryonic stem cells and then reintroduced into chimeras, thereby allowing examination of the effects of specific mutations on fetal and postnatal development. Abstract : Our studies show that high heteroplasmy deleterious mtDNA mutations presenting in mature mouse oocytes are eliminated during post-implantation development. The occurrence of purifying selection against deleterious mtDNA mutations during fetal development plays an important role in preventing the accumulation of pathogenic mutations that would cause consequences to species survival.